"I know you can do this" versus "How can you be so stupid?" Feedback among Chinese and American young adult friends. Issue 4 (1st September 2019) - Zhong, Xiaxin; Lee, Jeong Min; Morling, Beth
Abstract : According to past research, young adults prefer positive feedback from their friends, but emotional reactions to negative feedback are less severe in Korea than in the United States. We extended this past work in several ways: We studied both giving and receiving feedback, recruited Chinese young adults, used realistic scenarios, and employed the situation‐sampling method. Using text‐message‐based vignettes, Study 1 found that both American and Chinese friends used happy emojis when exchanging positive feedback whereas Americans used less positive emojis than did the Chinese when exchanging negative feedback. We then collected actual examples of feedback that people had given to their friends (Study 2a) and showed them to new samples of Chinese and American young adults (Study 2b). This situation‐sampling methodology found that (a) Americans rated negative feedback from both cultures especially negatively, and (b) negative feedback examples from China were rated especially negatively by people in both cultures. That is, although Chinese negative feedback is seemingly more harsh, Chinese young adults do not react as negatively.